Preparation method of high-strength and high-plasticity negative enthalpy titanium alloy material
By designing negative-enthalpy titanium alloy materials, using titanium, aluminum, vanadium, nickel and silicon elements, and using vacuum arc melting furnaces to prepare them, the contradiction between material strength and toughness is solved, and high-strength and high-plasticity material preparation is achieved, which has a wide range of applications. application potential.
Patent Information
- Application Number
- CN202410966765.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, increasing the strength of metal materials often leads to toughness loss, resulting in the problem of strength-toughness inversion, making it difficult to develop a material that has both high strength and high toughness.
By designing a negative-enthalpy titanium alloy material composed of titanium (Ti), aluminum (Al), vanadium (V), nickel (Ni) and silicon (Si), it is prepared using a vacuum arc melting furnace, and the element ratio is adjusted to Control the microstructure and mechanical properties.
It is possible to improve the toughness of the material while maintaining high strength, and obtain a high-strength and high-plasticity negative-enthalpy titanium alloy material, which is suitable for aerospace, marine ships, national defense and military and other fields.
Smart Images

Figure CN119332120A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to a method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material. Background Art
[0002] Metal structural materials, including titanium alloys, magnesium alloys, aluminum alloys and steel, are the base materials of advanced national defense weapons and high-precision equipment. Their excellent strength and toughness determine the advancement and safety of these equipment. However, the strength and toughness of materials are mutually restricted. When the strength is improved, the toughness is often lost, presenting a contradictory relationship of strength-toughness inversion. Developing metal structural materials with both high strength and high toughness has become a long-term pursuit of researchers.
[0003] The traditional alloy design chemical composition design concept is based on a "cocktail" trial and error method. Taking steel materials as an example, iron (Fe) is the basis, and a small amount of alloying elements are added to adjust its microstructure and performance to meet the needs of different service environments. For example, chromium (Cr) can increase the hardenability of steel and has a secondary hardening effect, which can improve the hardness and wear resistance of carbon steel without making the steel brittle. Nickel (Ni) can strengthen ferrite and refine pearlite, and the overall effect is to improve strength; refractory metal elements such as niobium (Nb) and tantalum (Ta) play a solid solution strengthening role and improve the strength of steel.
[0004] However, with the rapid development of modern science and technology and industry, it is urgent to develop materials with higher strength and plasticity to meet more stringent service environments, which poses a major challenge to the design and preparation requirements of alloy chemical composition.
[0005] In view of this, there is still room for further improvement in improving the high strength and high plasticity of negative enthalpy titanium alloy materials. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention proposes a method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material, which solves the technical problem in the prior art that the material often loses toughness while improving its strength.
[0007] The technical solution of the present invention is achieved in this way:
[0008] The present invention provides a method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material, comprising the following steps:
[0009] Ultrasonic cleaning is performed on each metal raw material of Ti, Al, V, Ni and Si, and the materials are mixed according to the mass percentage ratio, and they are placed in a water-cooled metal crucible in order from low to high melting points, with the metal raw material with the lowest melting point placed at the bottom layer and the metal raw material with the highest melting point placed at the surface layer, and titanium sponge is placed in one of the water-cooled metal crucibles;
[0010] Establish a vacuum oxygen-free environment and introduce protective gas;
[0011] Melting the metal raw materials in an oxygen-free environment until they are fully miscible, thereby obtaining the high-strength, high-plasticity, negative-enthalpy titanium alloy material;
[0012] Wherein, the high-strength and high-plasticity negative enthalpy titanium alloy material has a chemical formula of TiaAlbVcNidSie, and a, b, c, d and e correspond to the mass percentage ratios of the elements, a is 80-90wt%, b is 5-10wt%, c is 2-6wt%, d is 0-5wt%, and e is 0-2wt%;
[0013] The high-strength and high-plasticity negative enthalpy titanium alloy material has a chemical formula of Ti a Al b V c Ni d Si e ;
[0014] Wherein, a, b, c, d and e correspond to the mass percentage ratio of each element respectively, a is 80-90wt%, b is 5-10wt%, c is 2-6wt%, d is 0-5wt%, and e is 0-2wt%.
[0015] Based on this solution, it is further preferred that the chemical formula is Ti a Al b V c Ni d Si e Negative enthalpy titanium alloy material, the purity of the corresponding raw materials Ti, Al, V, Ni and Si is ≥99.95%.
[0016] On the basis of this solution, it is further preferred that the high-strength and high-plasticity negative enthalpy titanium alloy material has negative mixing enthalpy among the Ti, Al, V, Ni and Si elements.
[0017] Based on this solution, it is further preferred that the mixing enthalpy ΔH between the Ti, Al, V, Ni and Si elements mix They are:
[0018] ΔH mix (Ti-Al) = -30 kJ / mol, ΔH mix (Ti-V) = -2 kJ / mol, ΔH mix (Ti-Ni) = -35 kJ / mol,
[0019] ΔH mix (Ti-Si) = -66 kJ / mol, ΔH mix(Al-V) = -16 kJ / mol, ΔH mix (Al-Ni) = -22 kJ / mol,
[0020] ΔH mix (Al-Si) = -19 kJ / mol, ΔH mix (V-Ni) = -18 kJ / mol, ΔH mix (V-Si) = -48 kJ / mol, ΔH mix
[0021] (Ni—Si)=-40 kJ / mol.
[0022] On the basis of this solution, it is further preferred that the high-strength and high-plasticity negative enthalpy titanium alloy material is Ti 90 Al 6 V 4 、Ti 87.5 Al 8 V 4 Si 0.5 、Ti 86 Al 8 V 4 Ni 2 、Ti 85.5 Al 8 V 4 Ni 2 Si 0.5 and Ti 85 Al 8 V 4 Ni 2 Si 1 One of them.
[0023] On the basis of this solution, it is further preferred that the vacuum oxygen-free environment is established and the protective gas is introduced, specifically comprising the following steps:
[0024] Close the door of the arc melting furnace, turn on the circulating water and mechanical pump to evacuate. When the vacuum degree is lower than 5Pa, turn on the molecular pump to further evacuate. When the vacuum degree is lower than 5.0×10 -4 Pa, high-purity argon was introduced as the protective gas.
[0025] On the basis of this solution, it is further preferred that the arc melting of each metal raw material is carried out in an oxygen-free environment, wherein the arc melting of the titanium sponge is performed twice to absorb residual oxygen.
[0026] On the basis of this scheme, it is further preferred that the arc-strike melting of each metal raw material is carried out in an oxygen-free environment, wherein the number of arc-strike melting is greater than 4 times, and after each arc-strike melting, the cooled metal raw materials in the crucible are turned over before the next arc-strike melting, and before the next arc-strike melting of the alloy, the sponge titanium is arc-strike melted twice to absorb residual oxygen.
[0027] On the basis of this solution, it is further preferred that, in addition to the first arc melting and the last arc melting, other times of arc melting also include magnetic stirring of the metal raw materials.
[0028] On the basis of this solution, it is further preferred that the melting time of each arc melting is 1.0-2.0 min, and the melting voltage and melting current of the arc melting are 10-15 V and 300-350 A, respectively.
[0029] The method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material of the present invention has the following beneficial effects compared with the prior art:
[0030] The present invention provides a Ti a Al b V c Ni d Si e A series of negative enthalpy titanium alloy materials are composed of titanium, aluminum, vanadium, nickel and silicon elements and are made by a vacuum arc melting furnace. The series of negative enthalpy titanium alloys contain a body-centred cubic structure (BCC) and a hexagonal close packing structure (HCP), and the alloy microstructure and mechanical properties can be regulated by adjusting the element ratio; while in a typical dual-phase (BCC+HCP) titanium alloy, BCC is enriched in V elements and HCP is enriched in Ti and Al elements. Therefore, the addition of Ni elements with a relatively negative mixing enthalpy with V can promote the formation of BCC phases, thereby obtaining a higher volume fraction of BCC phases; at the same time, on the other hand, the mixing enthalpy of Si elements with Ti, Ni, Al, V and other elements is relatively negative, so that the Si element is evenly distributed. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 Ti described in the embodiment of the present inventiona Al b V c Ni d Si e Flow chart of the preparation method of negative enthalpy titanium alloy material;
[0033] Figure 2 Ti described in the embodiment of the present invention a Al b V c Ni d Si e X-ray diffraction pattern of negative enthalpy titanium alloy material;
[0034] Figure 3 Ti described in the embodiment of the present invention a Al b V c Ni d Si e Tensile stress-strain curve of negative enthalpy titanium alloy material. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] It should be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.
[0037] The present invention adopts a vacuum arc melting furnace to prepare Ti by designing a ratio of titanium (Ti), aluminum (Al), vanadium (V), nickel (Ni) and silicon (Si) elements. a Al b V c Ni d Si e Series of negative enthalpy titanium alloy materials.
[0038] Specifically, the present invention discloses a method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material, comprising the following steps:
[0039] Ultrasonic cleaning is performed on each metal raw material of Ti, Al, V, Ni and Si, and the materials are mixed according to the mass percentage ratio, and they are placed in a water-cooled metal crucible in order from low to high melting points, with the metal raw material with the lowest melting point placed at the bottom layer and the metal raw material with the highest melting point placed at the surface layer, and titanium sponge is placed in one of the water-cooled metal crucibles;
[0040] Establish a vacuum oxygen-free environment and introduce protective gas;
[0041] Melting the metal raw materials in an oxygen-free environment until they are fully miscible, thereby obtaining the high-strength, high-plasticity, negative-enthalpy titanium alloy material;
[0042] Wherein, the high-strength and high-plasticity negative enthalpy titanium alloy material has a chemical formula of TiaAlbVcNidSie, and a, b, c, d and e correspond to the mass percentage ratios of the elements, a is 80-90wt%, b is 5-10wt%, c is 2-6wt%, d is 0-5wt%, and e is 0-2wt%;
[0043] The high-strength and high-plasticity negative enthalpy titanium alloy material has a chemical formula of Ti a Al b V c Ni d Si e ;
[0044] Wherein, a, b, c, d and e correspond to the mass percentage ratio of each element respectively, a is 80-90wt%, b is 5-10wt%, c is 2-6wt%, d is 0-5wt%, and e is 0-2wt%.
[0045] Specifically, the Ti a Al b V c Ni d Si e The purity of the corresponding raw materials Ti, Al, V, Ni and Si is ≥99.95%.
[0046] Specifically, the high-strength and high-plasticity negative enthalpy titanium alloy material has negative mixing enthalpy among Ti, Al, V, Ni and Si elements.
[0047] Specifically, the mixing enthalpy ΔH between the Ti, Al, V, Ni and Si elements is mix They are:
[0048] ΔH mix (Ti-Al) = -30 kJ / mol, ΔH mix (Ti-V) = -2 kJ / mol, ΔH mix (Ti-Ni) = -35 kJ / mol,
[0049] ΔH mix (Ti-Si) = -66 kJ / mol, ΔH mix (Al-V) = -16 kJ / mol, ΔH mix (Al-Ni) = -22 kJ / mol,
[0050] ΔH mix (Al-Si) = -19 kJ / mol, ΔH mix (V-Ni) = -18 kJ / mol, ΔH mix (V-Si) = -48 kJ / mol, ΔH mix
[0051] (Ni—Si)=-40 kJ / mol.
[0052] Specifically, the vacuum oxygen-free environment is established and the protective gas is introduced, which specifically includes the following steps:
[0053] Close the door of the arc melting furnace, turn on the circulating water and mechanical pump to evacuate. When the vacuum degree is lower than 5Pa, turn on the molecular pump to further evacuate. When the vacuum degree is lower than 5.0×10 -4 Pa, high-purity argon was introduced as the protective gas.
[0054] Specifically, the arc-smelting of each metal raw material is performed in an oxygen-free environment, wherein the arc-smelting of the titanium sponge is performed twice to absorb residual oxygen.
[0055] Specifically, the arc-strike melting of each metal raw material is performed in an oxygen-free environment, wherein the number of arc-strike melting is greater than 4 times, and after each arc-strike melting, the cooled metal raw materials in the crucible are turned over before the next arc-strike melting, and the sponge titanium is arc-strike melted twice before the next arc-strike melting of the alloy to absorb residual oxygen.
[0056] Specifically, except for the first arc melting and the last arc melting, other times of arc melting also include magnetic stirring of the metal raw materials.
[0057] Specifically, the melting time of each arc melting is 1.0-2.0 min, and the melting voltage and melting current of each arc melting are 10-15 V and 300-350 A, respectively.
[0058] After the above optimization settings, the prepared series of negative enthalpy titanium alloys have a body-centered cubic structure and a close-packed hexagonal structure, and the Ti a Al b V c Ni d Si eThe series of negative enthalpy titanium alloy materials have both high strength and high plasticity in mechanical properties.
[0059] Example 1
[0060] A method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material comprises the following steps:
[0061] S1. Ultrasonic cleaning of metal raw materials of Ti, Al, V, Ni and Si is performed, and the materials are prepared according to the above mass percentage ratio, and they are placed in a water-cooled metal crucible in order of melting point from low to high, with the metal raw material with the lowest melting point placed at the bottom layer and the metal raw material with the highest melting point placed at the surface layer, and titanium sponge is placed in one of the water-cooled metal crucibles;
[0062] S2. Establish a vacuum oxygen-free environment and introduce protective gas;
[0063] S3. In an oxygen-free environment, arc melting is performed on the metal raw materials until they are fully miscible, thereby obtaining the high-strength and high-plasticity negative enthalpy titanium alloy material.
[0064] The chemical formula of the high-strength, high-plasticity, negative-enthalpy titanium alloy material is Ti 85 Al 8 V 4 Ni 2 Si 1 ;
[0065] Wherein, a, b, c, d and e correspond to the mass percentage ratio of each element respectively, a is 85wt%, b is 8wt%, c is 4wt%, d is 2wt% and e is 1wt%.
[0066] Specifically, the Ti 85 Al 8 V 4 Ni 2 Si 1 The purity of Ti, Al, V, Ni and Si of the corresponding raw materials is ≥99.95.
[0067] Specifically, the mixing enthalpy ΔH between the Ti, Al, V, Ni and Si elements is mix They are:
[0068] ΔH mix (Ti-Al) = -30 kJ / mol, ΔH mix (Ti-V) = -2 kJ / mol, ΔH mix (Ti-Ni) = -35 kJ / mol,
[0069] ΔH mix (Ti-Si) = -66 kJ / mol, ΔH mix (Al-V) = -16 kJ / mol, ΔHmix (Al-Ni) = -22 kJ / mol,
[0070] ΔH mix (Al-Si) = -19 kJ / mol, ΔH mix (V-Ni) = -18 kJ / mol, ΔH mix (V-Si) = -48 kJ / mol, ΔH mix
[0071] (Ni—Si)=-40 kJ / mol.
[0072] Specifically, the vacuum oxygen-free environment is established and the protective gas is introduced, which specifically includes the following steps:
[0073] Close the door of the arc melting furnace, turn on the circulating water and mechanical pump to evacuate. When the vacuum degree is lower than 5Pa, turn on the molecular pump to further evacuate. When the vacuum degree is lower than 5.0×10 -4 Pa, high-purity argon was introduced as the protective gas.
[0074] Specifically, the arc-smelting of each metal raw material is performed in an oxygen-free environment, wherein the arc-smelting of the titanium sponge is performed twice to absorb residual oxygen.
[0075] Specifically, the arc melting of each metal raw material is carried out in an oxygen-free environment, wherein the number of arc melting is greater than 4 times, and after each arc melting, the alloy in the crucible is turned over before the next arc melting, and the sponge titanium is melted and oxygen is absorbed twice before the next arc melting of the alloy.
[0076] Specifically, the arc melting time of each time is 1.0-2.0min, and except for the first arc melting and the last arc melting, the arc melting of the metal raw material also includes magnetic stirring of the melt, and the melting voltage and melting current of the arc melting are 10-15V and 300-350A respectively.
[0077] The Ti prepared in this example 85 Al 8 V 4 Ni 2 Si 1 The mixing enthalpy ΔH mix (Ti 85 Al 8 V 4 Ni 2 Si 1 )=-19.2 kJ / mol, yield strength is 1400 MPa, fracture strength is 1460 MPa, and tensile plasticity is 2.2%.
[0078] Example 2
[0079] A method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material comprises the following steps:
[0080] S1. Place high-purity raw material particles of Ti, V, Al, Ni and Si in an ultrasonic cleaner, wash them twice, and then accurately weigh and proportion them according to the molar ratio of the components, and place them in a water-cooled metal crucible in order from low to high melting points, with the element with the lowest melting point placed on the bottom layer and the element with the highest melting point placed on the top layer. At the same time, place titanium sponge in one of the water-cooled metal crucibles;
[0081] S2. Close the door of the arc melting furnace, turn on the circulating water and mechanical pump to evacuate. When the vacuum degree is lower than 5Pa, turn on the molecular pump to further evacuate. When the vacuum degree is lower than 5.0×10 -4 When Pa, high-purity argon is introduced as protective gas;
[0082] S3. Stir the arc in a high-purity argon atmosphere and melt the sponge titanium twice to absorb the residual oxygen in the furnace; first, use a large current for melting, at this time the melting voltage is 10-15V, the melting current is 300-350A, all the metal particles are melted and mixed evenly, after the alloy button is cast and cooled, it is turned over by a robot and melted in the same way, and magnetic stirring is turned on during each melting process after the second time. After each melting, the alloy button needs to be turned over 180 degrees, and a total of 4 meltings are performed, which can make the alloy composition more uniform. During the last melting, turn off the magnetic stirring to make it a smooth ingot, and perform suction casting; after the alloy button ingot is completely cooled, open the furnace door and take out the sample to obtain the high-strength and high-plasticity negative enthalpy titanium alloy material.
[0083] The chemical formula of the high-strength, high-plasticity, negative-enthalpy titanium alloy material is Ti 85.5 Al 8 V 4 Ni 2 Si 0.5 ;
[0084] Wherein, a, b, c, d and e correspond to the mass percentage ratio of each element respectively, a is 85.5wt%, b is 8wt%, c is 4wt%, d is 2wt% and e is 0.5wt%.
[0085] Specifically, the Ti 85.5 Al 8 V 4 Ni 2 Si 0.5 The purity of Ti, Al, V, Ni and Si of the corresponding raw materials is ≥99.95%.
[0086] The Ti prepared in this example 85.5 Al8 V 4 Ni 2 Si 0.5 Mixing enthalpy of alloy materials ΔH mix (Ti 85.5 Al 8 V 4 Ni 2 Si 0.5 )=-17.5kJ / mol, Ti 85.5 Al 8 V 4 Ni 2 Si 0.5 The room temperature tensile yield strength is 1200MPa, the breaking strength is 1300MPa, and the uniform elongation is 5.5%.
[0087] Example 3
[0088] A method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material comprises the following steps:
[0089] S1. Place high-purity raw material particles of Ti, V and Al in an ultrasonic cleaner respectively, clean them twice, then accurately weigh and proportion them according to the component ratio by molar ratio, and place them in a water-cooled metal crucible in order from low to high melting points, with the element with the lowest melting point placed on the bottom layer and the element with the highest melting point placed on the top layer. At the same time, place titanium sponge in one of the water-cooled metal crucibles;
[0090] S2. Close the door of the arc melting furnace, turn on the circulating water and mechanical pump to evacuate. When the vacuum degree is lower than 5Pa, turn on the molecular pump to further evacuate. When the vacuum degree is lower than 5.0×10 -4 When Pa, high-purity argon is introduced as protective gas;
[0091] S3. Stir the arc in a high-purity argon atmosphere and melt the sponge titanium twice to absorb the residual oxygen in the furnace; first, use a large current for melting, at this time the melting voltage is 10-15V, the melting current is 300-350A, all the metal particles are melted and mixed evenly, after the alloy button is cast and cooled, it is turned over by a robot and melted in the same way, and magnetic stirring is turned on during each melting process after the second time. After each melting, the alloy button needs to be turned over 180 degrees, and a total of 4 meltings are performed, which can make the alloy composition more uniform. During the last melting, turn off the magnetic stirring to make it a smooth ingot, and perform suction casting; after the alloy button ingot is completely cooled, open the furnace door and take out the sample to obtain the high-strength and high-plasticity negative enthalpy titanium alloy material.
[0092] The chemical formula of the high-strength, high-plasticity, negative-enthalpy titanium alloy material is Ti 90 Al 6 V4 ;
[0093] Wherein, a, b, c, d and e correspond to the mass percentage ratio of each element respectively, a is 90wt%, b is 6wt%, c is 4wt%, d is 0wt%, and e is 0wt%.
[0094] Specifically, the Ti 90 Al 6 V 4 The purity of Ti, Al and V of the corresponding raw materials is ≥99.95%.
[0095] The Ti prepared in this example 90 Al 6 V 4 Mixing enthalpy of alloy ΔH mix (Ti 90 Al 6 V 4 )=-11.1kJ / mol, Ti 90 Al 6 V 4 The room temperature tensile yield strength is 790 MPa, the breaking strength is 900 MPa, and the uniform elongation is 5.8%.
[0096] like Figure 1 As shown, Ti 90 Al 6 V 4 It is a typical dual-phase (BCC+HCP) titanium alloy, in which BCC is enriched with V, and HCP is enriched with Ti and Al. Therefore, the addition of Ni, which has a relatively negative mixing enthalpy with V, can promote the formation of BCC phase, thereby obtaining a higher volume fraction of BCC phase; secondly, the mixing enthalpy of Si with Ti, Ni, Al, V and other elements is relatively negative, so that Si element is evenly distributed.
[0097] Example 4
[0098] A method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material comprises the following steps:
[0099] S1. Place high-purity raw material particles of Ti, V, Al and Si in an ultrasonic cleaner, wash them twice, then accurately weigh and proportion them according to the component ratio by molar ratio, and place them in a water-cooled metal crucible in order from low to high melting points, with the element with the lowest melting point placed on the bottom layer and the element with the highest melting point placed on the top layer. At the same time, place titanium sponge in one of the water-cooled metal crucibles;
[0100] S2. Close the door of the arc melting furnace, turn on the circulating water and mechanical pump to evacuate. When the vacuum degree is lower than 5Pa, turn on the molecular pump to further evacuate. When the vacuum degree is lower than 5.0×10-4 When Pa, high-purity argon is introduced as protective gas;
[0101] S3. Stir the arc in a high-purity argon atmosphere and melt the sponge titanium twice to absorb the residual oxygen in the furnace; first, use a large current for melting, at this time the melting voltage is 10-15V, the melting current is 300-350A, all the metal particles are melted and mixed evenly, after the alloy button is cast and cooled, it is turned over by a robot and melted in the same way, and magnetic stirring is turned on during each melting process after the second time. After each melting, the alloy button needs to be turned over 180 degrees, and a total of 4 meltings are performed, which can make the alloy composition more uniform. During the last melting, turn off the magnetic stirring to make it a smooth ingot, and perform suction casting; after the alloy button ingot is completely cooled, open the furnace door and take out the sample to obtain the high-strength and high-plasticity negative enthalpy titanium alloy material.
[0102] The chemical formula of the high-strength, high-plasticity, negative-enthalpy titanium alloy material is Ti 87.5 Al 8 V 4 Si 0.5 ;
[0103] Wherein, a, b, c, d and e correspond to the mass percentage ratio of each element respectively, a is 87.5wt%, b is 8wt%, c is 4wt%, d is 0wt%, and e is 0.5wt%.
[0104] Specifically, the Ti 87.5 Al 8 V 4 Si 0.5 The purity of the corresponding raw materials Ti, Al, V and Si is ≥99.95%.
[0105] The Ti prepared in this example 87.5 Al 8 V 4 Si 0.5 Mixing enthalpy of alloy materials ΔH mix (Ti 87.5 Al 8 V 4 Si 0.5 )=-15.6kJ / mol, Ti 87.5 Al 8 V 4 Si 0.5 The room temperature tensile yield strength is 850 MPa, the breaking strength is 1000 MPa, and the uniform elongation is 6.9%.
[0106] Example 5
[0107] A method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material comprises the following steps:
[0108] S1. Place high-purity raw material particles of Ti, V, Al, and Ni in an ultrasonic cleaner, wash them twice, and then accurately weigh and proportion them according to the molar ratio of the components, and place them in a water-cooled metal crucible in order from low to high melting points, with the element with the lowest melting point placed on the bottom layer and the element with the highest melting point placed on the top layer. At the same time, place titanium sponge in one of the water-cooled metal crucibles;
[0109] S2. Close the door of the arc melting furnace, turn on the circulating water and mechanical pump to evacuate. When the vacuum degree is lower than 5Pa, turn on the molecular pump to further evacuate. When the vacuum degree is lower than 5.0×10 -4 When Pa, high-purity argon is introduced as protective gas;
[0110] S3. Stir the arc in a high-purity argon atmosphere and melt the sponge titanium twice to absorb the residual oxygen in the furnace; first, use a large current for melting, at this time the melting voltage is 10-15V, the melting current is 300-350A, all the metal particles are melted and mixed evenly, after the alloy button is cast and cooled, it is turned over by a robot and melted in the same way, and magnetic stirring is turned on during each melting process after the second time. After each melting, the alloy button needs to be turned over 180 degrees, and a total of 4 meltings are performed, which can make the alloy composition more uniform. During the last melting, turn off the magnetic stirring to make it a smooth ingot, and perform suction casting; after the alloy button ingot is completely cooled, open the furnace door and take out the sample to obtain the high-strength and high-plasticity negative enthalpy titanium alloy material.
[0111] The chemical formula of the high-strength, high-plasticity, negative-enthalpy titanium alloy material is Ti 86 Al 8 V 4 Ni 2 ;
[0112] Wherein, a, b, c, d and e correspond to the mass percentage ratio of each element respectively, a is 86wt%, b is 8wt%, c is 4wt%, d is 2wt%, and e is 0wt%.
[0113] Specifically, the Ti 86 Al 8 V 4 Ni 2 The purity of the corresponding raw materials Ti, Al, V and Ni is ≥99.95%.
[0114] The Ti prepared in this example 86 Al 8 V 4 Ni 2 Mixing enthalpy of alloy ΔH mix (Ti 86 Al8 V 4 Ni 2 )=-15.8kJ / mol, where Ti 86 Al 8 V 4 Ni 2 The room temperature tensile yield strength is 1200 MPa, the breaking strength is 1310 MPa, and the uniform elongation is 4.5%.
[0115] Figure 2 Ti prepared in Example 1-5 a Al b V c Ni d Si e X-ray diffraction patterns of a series of negative enthalpy titanium alloy materials, Figure 2 As can be seen, the obtained Ti a Al b V c Ni d Si e Negative enthalpy titanium alloy materials all contain a dual-phase structure of BCC+HCP, and no other new phases are produced. At the same time, with the increase of Ni element content, the volume fraction of BCC phase also increases.
[0116] Figure 3 Ti prepared in Example 1-5 a Al b V c Ni d Si e The tensile stress-strain curves of a series of negative enthalpy titanium alloy materials at room temperature, such as Figure 3 As shown, with the addition of negative enthalpy elements Ni and Si, the alloy strength is improved and has greater tensile toughness.
[0117] In summary, the present invention provides a method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material, and can control the alloy microstructure and mechanical properties by adjusting the element ratio. It has great application potential in major fields such as aerospace, marine ships, and national defense and military.
[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-strength and high-plasticity negative enthalpy titanium alloy material, characterized in that: The following steps are involved: Ultrasonic cleaning is performed on each metal raw material of Ti, Al, V, Ni and Si, and the materials are prepared according to the mass percentage ratio, and they are placed in a water-cooled metal crucible in order from low to high melting points, with the metal raw material with the lowest melting point placed at the bottom layer and the metal raw material with the highest melting point placed at the surface layer, and sponge titanium is placed in one of the water-cooled metal crucibles; Establish a vacuum oxygen-free environment and introduce protective gas; Melting the metal raw materials in an oxygen-free environment until they are fully miscible, thereby obtaining the high-strength, high-plasticity, negative-enthalpy titanium alloy material; The high-strength, high-plasticity, negative-enthalpy titanium alloy material has a chemical formula of Ti a Al b V c Ni d Si e , a, b, c, d and e correspond to the mass percentage ratio of each element, a is 70-90wt%, b is 3-15wt%, c is 1-10wt%, d is 0-10wt%, and e is 0-10wt%.
2. The method for preparing a high-strength, high-plasticity, negative-enthalpy titanium alloy material according to claim 1, characterized in that: The chemical formula is Ti a Al b V c Ni d Si e Negative enthalpy titanium alloy material, the purity of the corresponding raw materials Ti, Al, V, Ni and Si elements is ≥99.95%.
3. The method for preparing a high-strength, high-plasticity, negative-enthalpy titanium alloy material according to claim 1, characterized in that: The high-strength and high-plasticity negative-enthalpy titanium alloy material has negative mixing enthalpy among Ti, Al, V, Ni and Si elements.
4. The method for preparing a high-strength, high-plasticity, negative-enthalpy titanium alloy material according to claim 3, characterized in that: The mixing enthalpy ΔH between the Ti, Al, V, Ni and Si elements mix They are: ΔH mix (Ti-Al)G-30kJ / mol,ΔH mix (Ti-V)0-2kJ / mol,ΔH mix (Ti-Ni)-35kJ / mol, ΔH mix (Ti-Si)-66kJ / mol,ΔH mix (Al-V)N-16kJ / mol,ΔH mix (Al-Ni)-22kJ / mol, ΔH mix (Al-Si)=-19kJ / mol,ΔH mix (V-Ni)=-18kJ / mol,ΔH mix (V-Si)=-48kJ / mol,ΔH mix (Ni—Si)=-40 kJ / mol.
5. The method for preparing a high-strength, high-plasticity, negative-enthalpy titanium alloy material according to claim 1, characterized in that: The negative enthalpy titanium alloy material with high strength and high plasticity is Ti 90 Al6V4、Ti 87.5 Al8V4Si 0.5 、Ti 86 Al8V4Ni2、Ti 85.5 Al8V4Ni2Si 0.5 and Ti 85 One of Al8V4Ni2Si1.
6. The method for preparing a high-strength, high-plasticity, negative-enthalpy titanium alloy material according to claim 1, characterized in that: The vacuum oxygen-free environment is established and the protective gas is introduced, specifically comprising the following steps: Close the door of the arc melting furnace, turn on the circulating water and mechanical pump to evacuate. When the vacuum degree is lower than 5Pa, turn on the molecular pump to further evacuate. When the vacuum degree is lower than 5.0×10 -4 Pa, high-purity argon was introduced as the protective gas.
7. The method for preparing a high-strength, high-plasticity, negative-enthalpy titanium alloy material according to claim 1, characterized in that: The arc-smelting of the metal raw materials in an oxygen-free environment is performed, wherein the arc-smelting of the titanium sponge is performed twice to absorb residual oxygen.
8. The method for preparing a high-strength, high-plasticity, negative-enthalpy titanium alloy material according to claim 1, characterized in that: The arc-smelting of each metal raw material in an oxygen-free environment is performed more than 4 times. After each arc-smelting, the cooled metal raw materials in the crucible are turned over before the next arc-smelting. Before the next arc-smelting of the alloy, the sponge titanium is arc-melted twice to absorb residual oxygen.
9. The method for preparing a high-strength, high-plasticity, negative-enthalpy titanium alloy material according to claim 8, characterized in that: In addition to the first arc-starting melting and the last arc-starting melting, the other arc-starting melting also includes magnetic stirring of the metal raw materials.
10. The method for preparing a high-strength, high-plasticity, negative-enthalpy titanium alloy material according to claim 9, characterized in that: The smelting time of the arc smelting is 1.0-2.0 min, and the smelting voltage and smelting current of the arc smelting are 10-15 V and 300-350 A respectively.